PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA MELALUI STRATEGI PEMBELAJARAN LIGHTENING THE LEARNING CLIMATE - Jean Amorie, author (JURNAL E-DUMATH, 2015)
The problems of this research is a low the student learning result. This is due to the lack of involvement of the students and the students just accept what is presented by the teacher rather than seek their own knowledge that students need. One way to overcome this problem is by actively engaging students while learning. The aims of this research are to improve the student learning result with using the learning strategies of lightening the learning climate. This research is an action research with three cycles, which consists of planning, implementation, observation and reflection, where each cycle consists of two meetings. The subjects of this study were students in fifth grade of the MI Islamiyah Sinar Jaya. The data used in this research is qualitative and quantitative data. The results of the research in the first, second, and third cycle students who received grades â¥ KKM on the first cycle of 47.2%, the second cycle of 58.5%, and 80.6% for the third cycle. The results showed that the learning strategy of lightening the learning climate can improve mathematics student learning on the subject Build Flat in fifth grade of MI Islamiyah Sinar Jaya in the academic year of 2011/2012..Keywords: The Student Learning Result, The Learning Strategis of Lightening The Learning Climate, The Subject of Build Flat